Hosting Virtual Reality in Museums: a critical approach - Shehade, Maria; Stylianou-Lambert, Theopisti (My University, 2020)
The past few years have seen a big increase in the use of Virtual Reality in museum environments in an attempt for museums to embrace technological innovations and adapt to the challenges of the digital era. A considerable corpus of literature is available exploring the advantages of VR in museums in terms of alternative content delivery, the customisation of museum experiences and visitor participation, amongst others. However, most of these studies tend to overemphasise the advantages of these technologies and overlook the challenges or limitations created by the adoption of VR in the museum environment. Moreover, most of these studies, focus on the visitors’ experience and perceptions and don’t examine the needs or opinions of museum professionals who are responsible for the objects and narratives of a museum. Thus, the aim of this presentation is to explore the opinions and experiences of museum professionals on the use of VR technology in museums, their visions for the future of technology in museums and the possible advantages or limitations of such technologies. The presentation will provide an in-depth analysis of interviews with museum professionals from a number of countries around the world who shared their experiences with particular VR projects. The ultimate aim is to offer a more critical and holistic examination and assessment of the use of VR in museums, to explore how the identified challenges can be overcome and to investigate whether VR can challenge traditional museological values and affect the very nature of the museum experience offered to visitors.
Keywords: Virtual reality; Museum